Lingoactive 1.0: integrating the Italian language and exercise in a fun game - Kram, Suhardi; Wan Chik, Wan Firdaus; Robert Budull, Cyndra; Sabturani, Noreriani; James, Adjullea; Ahing, Theresa; Catarinella, Piermauro (Universiti Teknologi MARA, Kedah, 2023)
In a world that is increasingly digital and fast-paced, finding innovative ways to combine education, entertainment, and physical activity holds significant importance. The “Lingoactive 1.0: Integrating Italian Language and Exercise in a Fun Game” is a creative and engaging board game that seamlessly merges language learning, physical exercise, and social interaction. Traditional language learning methods often struggle to captivate learners' attention, leading to waning motivation and limited retention. Concurrently, the sedentary nature of learning exacerbates the growing health concerns posed by physical inactivity. Newlearners of the Italian language often find themselves susceptible to boredom and swift forgetfulness of Italian terms when studying in a manner without practice it in a fun way. This underscores the significance of incorporating innovative language games into the learning process, as it cultivates attachment and interest. This highlights the necessity for learners to immerse themselves in a dynamic and enjoyable environment, surrounded by a community of individuals sharing the goal of mastering the language. Such an environment encourages not only mental engagement but also physical activity, ensuring a comprehensive and fulfilling learning experience (Nakao, 2019).The game play for this board game isplayers will navigate the board with dice, encountering exercises tied to Italian terms. A QR- coded video accompanies each exercise, offering visual and auditory guidance, thereby fostering immersive learning. Players progress through rounds, performing exercises corresponding to landed spaces, cultivating both language proficiency and physical vitality. The game introduces interactive Q&A segments, promoting social interaction. Successfully answering questions rewards players, while incorrect responses lead to entertaining penalties, adding an element of excitement. The winner will be the individual who completes the 5 rounds first. The combination of English and Italian language will make this product universal. By using the English and Italian languages as the primary mediums of communication, this product attains universality, rendering it accessible and beneficial to individuals worldwide.